Analisis Struktur Modal Dan Kinerja Operasi Dalam Prediksi Kondisi Financial Distress Sektor Tambang Batubara Go Public - Victor Agustinus Tampubolon (Postgraduate of Jayabaya University, 2015)
This research aims to provide an overview of the growth of the coal mining sector in Indonesia. The background of the enormous potential for the Earth Indonesia owned and empowered as much as possible because it will contribute greatly to the private sector and economic growth in Indonesia. Many private companies that manage coal mining by leaving various problems both externally and internally. Externally many mining companies that do not perform reclamation and CSR (Corporate Social Responsibility). Internally liquidity obligations that can not be run and even lead to bankruptcy. This prompted the authors to examine the extent to which the management company - coal mining companies in managing the company’s financial and operating performance.